Seasonal patterns of taxonomic and functional beta diversity in submerged macrophytes at a fine scale. Issue 14 (24th June 2021) - Wang, Hao; Fu, Hui; Wen, Zihao; Yuan, Changbo; Zhang, Xiaolin; Ni, Leyi; Cao, Te
Abstract: Spatiotemporal variation in community composition is of considerable interest in ecology. However, few studies have focused on seasonal variation patterns in taxonomic and functional community composition at the fine scale. As such, we conducted seasonal high‐density sampling of the submerged macrophyte community in Hongshan Bay of Erhai Lake in China and used the generalized dissimilarity model (GDM) to evaluate the effects of environmental factors and geographic distance on taxonomic and functional beta diversity as well as corresponding turnover and nestedness components. At the fine scale, taxonomic turnover and nestedness as well as functional turnover and nestedness showed comparable contributions to corresponding taxonomic and functional beta diversity, with different importance across seasons. All taxonomic and functional dissimilarity metrics showed seasonal variation. Of note, taxonomic beta diversity was highest in summer and lowest in winter, while functional beta diversity showed the opposite pattern. Taxonomic and functional turnover showed similar change patterns as taxonomic and functional beta diversity. Taxonomic nestedness was low in summer and high in winter. Functional nestedness was also lower in summer. These results suggest that under extreme environmental conditions, both turnover and nestedness can exist at the fine scale and seasonal community composition patterns in submerged macrophytes should be considered. Future investigations on community assembly mechanisms should pay greater attention to long‐term dynamic characteristics and functional information. Abstract : Both turnover and nestedness driven the spatial dissimilarity either from taxonomic or functional perspective in fine scale. Taxonomic and functional beta diversity, taxonomic and functional turnover, and taxonomic and functional nestedness all presented seasonal variations. Environmental variables rather than geographic distance dominated spatial variations of community assemblage in a fine scale.